The Subjective Significance Of Raising Military Ethos - Kakharov Siyavish (Euro Asian Journal Publishing, 2025)
This article pedagogically reveals the influence of military ethics on the development of military culture through social values and spiritual-ideological processes. Military culture is an integral part of the entire social culture and, as a multi-level phenomenon, can be expressed in special features (military customs, military rituals and symbols, texts).
Keywords: Military culture; ethos; ideology